Expression of NELL2/NICOL-ROS1 lumicrine signaling-related molecules in the human male reproductive tract - Daiji Kiyozumi (BMC, 2024)
Abstract The maturation of spermatozoa is a regulated process, influenced by genes expressing essential secreted proteins in the proximal epididymis. Recent genetic studies in rodents have identified the non-sex steroidal molecular signals that regulate gene expression in the proximal epididymis. Germ cells in the testis secrete ligand proteins into the seminiferous tubule lumen The ligand proteins travel through the male reproductive tract lumen to the epididymis, where they bind to receptors, triggering the differentiation of the luminal epithelium for sperm maturation. It is, however, not fully unveiled if such a testis-epididymis trans-luminal signaling mechanism exists in other species, especially humans. In the present study, the rodent-type testis-epididymis trans-luminal signaling in the human male reproductive tract was evaluated in a step-by-step manner by analyzing testis and epididymis gene expression and signaling mediator protein function. There was a significant correlation between the epididymal expressions of mouse genes upregulated by the trans-luminal signaling and those of their human orthologs, as evaluated by the correlation coefficient of 0.604. The transcript expression of NELL2 and NICOL encoding putative ligand proteins was also observed in human testicular cells. In vitro experiments demonstrated that purified recombinant human NELL2 and NICOL formed a molecular complex with similar properties to rodent proteins, which was evaluated by a dissociation equilibrium constant of 110 nM. Recombinant human NELL2 also specifically bound to its putative receptor human ROS1 in vitro. Collectively, these findings suggest that the rodent-type testis-epididymis secreted signaling mechanism is also possible in the human male reproductive tract.